N027 Telephone/email service provided to IBD patients by Canadian IBD nurses. (16th January 2018) - Chauhan, U; Nistor, O –I; Currie, B; Nicholl, J; McCaw, W; Watson, M; Westin, L; Fernandes, A; Norton, C
Abstract: Background: Inflammatory bowel disease (IBD) is a chronic disease characterized by periods of illness and remission. The disease course can be unpredictable and challenging to treat. This can have negative impacts on patients' quality of life and lead to increased health care utilisation. Given the complex and unpredictable disease course, patients' can require assessment that may not coincide with scheduled office visits. Nurses play an integral role in providing access to health care between office visits. The primary objective of this study was to examine the utilisation of IBD nursing telephone/email service provided to IBD patients during a 14-day period in Canada. Methods: Using a survey study design, data were collected by Canadian IBD (CANIBD) Nurses conducting an audit of telephone/email services provided by IBD nurses over a 2-weeks period. Gender, diagnosis, reason and length of call, action taken and probable healthcare utilisation were collected. The nurses' interactions with IBD patients were compared using paired and independent t -tests. Results: Eighty-four IBD nurses across Canada were invited to participate in the study; 21 nurses participated in the study, including 4 research nurses, 7 adult Registered Nurses (RN), and 2 paediatric RNs, 2 Clinical Nurse Specialists (CNS), 6 Nurse Practitioners (NP) (4 adults and 2 paediatric) with good representation from across the country. Five hundred and Seventy-two encounters were reported: 93 (16%) via email, 443 (77%) via telephone and 36 (6%) telephone conversation following email interaction. The reasons for the telephone/email contact were divided into 8 categories: disease flare, other gastrointestinal (GI) symptoms, medication-related concerns, follow-up with investigation results, scheduling appointments, questions related to insurance coverage, psychosocial concerns, and financial concerns. Because of IBD nurses' interaction with patients, nurses were able to independently manage 61% of patient inquiries while 19% required additional clinician consultation. For further attention, 20% were scheduled in IBD clinic and 11% required follow-up phone call. Conclusions: A small proportion of IBD nurses in Canada offer telephone/email access to care for IBD patients. Although 84 IBD nurses were invited to participate in this outpatient IBD nursing practice audit, only 21 completed the survey. IBD nurses are a critical point of contact for patients and our study identified and compared common reasons for call in the adult and paediatric settings. Nurses were able independently manage the "reason for call" in 61% of the time. Further research would be valuable to explore the impact that IBD nurses have on the wellbeing of patients with IBD and their healthcare utilisation.